2004
DOI: 10.1093/aob/mci054
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Internal Nitrogen Stores in the Rhizomatous Grass Calamagrostis epigejos During Regrowth After Defoliation

Abstract: Production of new leaf area was entirely reliant, during the first week after defoliation, on N stores present in the plant. Mobilized N originated mainly from free amino acids and soluble proteins located in roots, and less so from proteins in stubble. Presence of VSP in the roots was not confirmed. The data suggest that rhizomes played an important role in N transport but not in N storage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 24 publications
(31 reference statements)
3
25
0
Order By: Relevance
“…The content of saccharides and soluble protein decreased in roots after defoliation to the similar levels in all N treatments ( Table 1). Decline of protein content in roots of C. epigejos during regrowth after defoliation has been shown previously, although no specialized vegetative storage proteins were found (Kavanová and Gloser 2005).…”
Section: Contents Of Storage Compounds After Regrowthsupporting
confidence: 67%
See 1 more Smart Citation
“…The content of saccharides and soluble protein decreased in roots after defoliation to the similar levels in all N treatments ( Table 1). Decline of protein content in roots of C. epigejos during regrowth after defoliation has been shown previously, although no specialized vegetative storage proteins were found (Kavanová and Gloser 2005).…”
Section: Contents Of Storage Compounds After Regrowthsupporting
confidence: 67%
“…We observed the most important changes in roots (frequently source of mobilized reserves in grasses, Ourry et al 1988, Volenec et al 1996, Kavanová and Gloser 2005 and stubble base that acts predominantly as sink for mobilized compounds during regrowth. The content of saccharides and soluble protein decreased in roots after defoliation to the similar levels in all N treatments ( Table 1).…”
Section: Contents Of Storage Compounds After Regrowthmentioning
confidence: 90%
“…A similar 2-year lag between the start of the mowing and the decrease of C. epigejos was reported by Lehmann and Rebele (2002) from a different habitat. The slow decrease can be attributed to the nutrient reserves accumulated in the rhizomes of this species (Klimes & Klimesova 2002;Fiala et al 2003;Kavanová & Gloser 2005).…”
Section: Discussionmentioning
confidence: 95%
“…Consequently, in the present situation, differences in survival and regrowth of stems could involve differences in the nature of the resources stored. Indeed, the nature of resources stored is partly ruled by the nutrient level of the habitat where the plant has grown (Fischer et al 1995;Améziane et al 1997;Cuzzuol et al 2005;Kavanova and Gloser 2005). For instance, in nutrient-rich habitats, Steinbáchová-Vojtísková et al (2006) demonstrated that Typha individuals tend to store more nitrogen and non-structural carbohydrates, whereas in oligotrophic conditions, individuals of Phragmites accumulate preferably starch (Kubin and Melzer 1996).…”
Section: Stem Survival and Regeneration After Disturbancementioning
confidence: 99%